RELATIONSHIP BETWEEN HELICOBACTER PYLORI INFECTION IN TYPE 2 DIABETES MELLITUS PATIENTS BASED ON ANTI IgA AND ANTI IgG HELICOBACTER PYLORI - Gita Siallagan, Ricke Loesnihari & Taufik Sungkar (International Journal of Research Science and Management, 2020)
Background Helicobacter Pylori (H. Pylori) infection is an infectious disease of the gastrointertinal tract especially the stomach and is currently associated with various systemic disorders in the body, one of which is hormonal disorders. Diabetes mellitus (DM) is an important cause of dyspepsia. Impaired gastrointestinal motor function is now recognized as a major problem in diabetes mellitus. The incidence of H. Pylori is increased in DM. Delayed gastric emptying and dysmotility are important causes of dyspepsia in diabetes. Methods This study was conducted by cross sectional method. The sample of the study was 39 patients who met the inclusion and exclusion criteria in the General Hospital H. Adam Malik Medan. Anti IgA and anti IgG H. Pylori examination by ELISA method using Chemwell. Results There were no difference in the incidence of anti IgA H. Pylori positive in patients with controlled DM and uncontrolled DM with p= 0,431. There was no difference in the incidence of anti IgA H. Pylori positive in patients with controlled DM and uncontrolled DM with p= 0,423. However, there were differences in H.Pylori infection in DM patients with dyspepsia and DM patients without dyspepsia with p = 0.001. Conclusion There were no relationship between H. Pylori infections in patients with type 2 DM